(untitled) (Third Sector Social Economic Review, 2023)
The resources of people in organizations play an important role in ensuring competition. Problems that arise due to human factors are important for institutions and organizations providing health services. Because of the institutions and organizations that provide health services, it is very difficult to tolerate even the smallest problem that arises in these organizations from those that directly spread human life. One of the problems in organizations that offer these services is presenteeism and employment motivations that are thought to cause presenteeism. For this reason, this study was conducted to determine the relationship between presenteeism and motivation, which is considered to be very important in the health service sector. The population of the study consists of 170 employees of a private hospital in Ankara. In the study, 95% confidence interval was reached to 119 health workers with the convenience method. In the study, the “Standford Presenteeism Scale” and the “Motivation to work” strategies were used. In the study, limitations and regression analyzes were performed for the purpose of testing the assumptions, and as a result of the structured scaled analysis, among the six dimensions of presenteeism and motivation, hygiene, and motivation affective dimensions were considered to be positive target targets with 0.05 possibilities. In addition, according to the regression analysis group, the increase in the perceptions of presenteeism caused an increase in the motivation of the employees. As a result of the analyses, hypotheses H1, H2, H3, and H4 were accepted.